ADOPTION OF DIGITAL TECHNOLOGIES AND REDUCTION OF THE DIGITAL DIVIDE AMONG VULNERABLE GROUPS IN THE EUROPEAN UNION - Kotarac, Đorđe; Mitrović, Đorđe; Stevanović, Simo (Economics of Agriculture, 2025)
In the endogenous theory of economic growth, technological progress is viewed as a crucial factor in the economic development of countries. The advancement of digital technologies and ICT innovations underpins sustainable economic growth over the long term. However, the rapid digital development of the population has not been distributed evenly across all social cohorts. The digital divide stems from insufficient adoption of technology by vulnerable groups. The paper assesses internet use, access to digital devices, and digital skill acquisition among vulnerable groups. The methodological approach includes the computation of the Digital Development Index (“IDA Index”) and the Digital Divide Index (“DIDIX Index”). The results indicate substantial growth in digital technology adoption and a reduction of the digital divide among vulnerable groups in EU (27) countries. The research demonstrates the emergence of the second-level digital divide, marked by broad access to digital technologies and devices, alongside persistent gaps in the digital competencies required for their effective utilization.